1963
DOI: 10.1002/j.2050-0416.1963.tb01930.x
|View full text |Cite
|
Sign up to set email alerts
|

Wort From Green Malt and Unmalted Cereals

Abstract: Laboratory investigations of the quality of worts produced from green malt, from mixed grists of green malt and unmalted cereals, and by the action of commercial enzymes on barley starch are described. Green malt alone gives sweet worts which are very highly fermentable and contain much nitrogenous material but are of very reduced anthocyanogen content. Satisfactory yields of extract are obtained in the conversion of unmalted cereals by green malt if they are finely ground. Additional treatment such as presoak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
0

Year Published

1968
1968
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 2 publications
(2 reference statements)
3
18
0
Order By: Relevance
“…β‐amylase, which is present in bound form in unmalted barley, suffered a considerable loss during kilning from 15.3 ± 0.3 to 9.7 ± 0.5 BU after kilning, whereas α‐Amylase, in accordance with the literature , was more thermostable with little loss in enzyme activity across kilning. These results support the hypothesis , that there is a good potential to generate highly fermentable worts using green malt.…”
Section: Resultssupporting
confidence: 89%
“…β‐amylase, which is present in bound form in unmalted barley, suffered a considerable loss during kilning from 15.3 ± 0.3 to 9.7 ± 0.5 BU after kilning, whereas α‐Amylase, in accordance with the literature , was more thermostable with little loss in enzyme activity across kilning. These results support the hypothesis , that there is a good potential to generate highly fermentable worts using green malt.…”
Section: Resultssupporting
confidence: 89%
“…Wort derived from undried malt has a "raw" aroma and flavour. MacWilliam et al 6 found that this could be removed by boiling at either atmospheric or reduced pressure until the wort volume was reduced by 10%. In the process described here the wort is boiled both at atmospheric and reduced pressure and its volume reduced by about 80%.…”
Section: Discussionmentioning
confidence: 99%
“…These polyphenols are also attacked by anthocyanogenase-type enzymes during the mashing, resulting in a wort with far lower anthocyanogen content than worts from conven tionally kilned malts. 6 The elimination of diastatic power by boiling is not considered a drawback as this syrup is designed for direct entry into the copper. The final product is taken off at 78 to 80% solids at an S.G. of around 1-4 and a viscosity at 20°C.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, green malt is not microbiologically stable, hence it needs to be either processed directly, by mashing in immediately, or by reducing its moisture content to a microbiologically safe level. On the other hand, green malt is rich in diastase enzymes, with great capacity, for example, to convert the starch of unmalted adjuncts into fermentable sugars ( 12, 13 ) . Additionally, the extra enzymatic potential of green malt could potentially be suitable for mashing in less time.…”
Section: Introductionmentioning
confidence: 99%
“…Previous researchers ( 12, 13, 20 ) have reported that wort and beer of acceptable quality could be produced from green malt, provided a suitable mill was used. Unfortunately, no detailed brewing protocol or assessment of the resulting beer flavour or its’ stability were published in these papers which date back to the 1960's.…”
Section: Introductionmentioning
confidence: 99%